Violencia y lo sagrado (Theological Kronos, 2019)
In the following article are gathered the conferences given in the colloquium: the violence and the sacred, in the Baptist University, because of the Martin Luther King Chair. The lectures by Professor Roberto Caicedo, Professor Jairo Racines and Professor César Moya. The conferences to deal with the violence from the interpretation of René Girard, the holy according to Rudolf Otto and the founding myth of Cain and Abel from biblical criticism. Each topic is presented respectively according to the order of the aforementioned speakers. The purpose of the studio and the present article is to read the Colombian reality in accordance with the biblical text and with the hermeneutical approaches to violence and the sacred from René Girard and Rudolf Otto.
Keywords: Violence; Life; the Holy; Sacrifice; Memory; No repetition